Cancer and Cachexia: influence of a therapeutic exercise protocol on the health and disease process (Research, Society and Development, 2020)
Cancer is a clinical condition resulting from disordered cell proliferation, and has its association with cachexia, in part of the cases, this condition ends up worsening the patient's condition, due to the intense depletion of lean mass and adipose tissue, which causes immunological changes that compromise the effectiveness of drug therapy. Objective: This study aimed to evaluate the therapeutic effects of the application of resistance exercises of moderate intensity in cachectic patients with cancer of the gastrointestinal tract. Methodology: 20 healthy and sedentary individuals were selected for the control group, with an age range similar to the test group, which consisted of 20 cancer patients with gastrointestinal cancer, associated with cachexia, and the evaluations were performed with the following instruments: load cell, nutritional analysis of the menu, total energy value (VET), basal metabolic rate (BMR). The menu and motor control were evaluated before and after the resistance exercise protocol, compared to a group of normal people without association with the pathology and after the exercise protocol, the group of patients demonstrated an increase and strength control that approached the healthy group, being statistically significant Results: Some patients did not have the adequate caloric intake both when comparing the basal metabolic rate and when adding an exercise practice, visualized through the calculation of the total energy value, about the strength assessment, there was a significant improvement between the first and second evaluation, although the protocol time was not enough for lean mass production. Conclusion: The results found suggest that this treatment should be applied for longer than the one developed to assess whether the caloric intake was adequate, and if the proposed protocol would be effective for the production of muscle mass in these patients who have severe catabolic processes, evaluating the biological individuality of each patient, thus meeting the metabolic needs.